Intrauterine Pressure Catheter Use Is Associated with an Increased Risk of Postcesarean Surgical Site Infections - Gee, Stephen E.; Ma'ayeh, Marwan; Ward, Calvin; Buhimschi, Catalin; Klebanoff, Mark; Rood, Kara (American Journal of Perinatology, 2020)
Objective This study aimed to determine if intrapartum placement of an intrauterine pressure catheter (IUPC) is associated with an increased rate of surgical site infections in women undergoing a cesarean delivery.Study Design This was a secondary analysis of the prospective observational Maternal–Fetal Medicine Units Network Vaginal Birth after Cesarean Registry. We compared patients with and without IUPC use. A multivariable logistic regression was performed to evaluate for an association between IUPC use and postcesarean surgical site infections.Results The study included 16,887 women: 7,441 with IUPC use and 9,446 without IUPC use. After adjustment for potential cofounders, IUPC use was associated with an increased risk of postcesarean infections compared with those without IUPC use (adjusted odds ratio: 1.28; 95% confidence interval: 1.10–1.50; p = 0.002).Conclusion IUPC use is associated with an increased risk of postcesarean surgical site infections. This supports the judicious use of IUPC for limited clinical indications and provides a potential area of focus for reduction in postcesarean infections.
Keywords: intrauterine pressure catheter; cesarean; surgical site infection; SSI; postoperative